ANALISIS KANDUNGAN GIZI DAN ORGANOLEPTIK MIE KERING SUBSTITUSI TEPUNG KACANG HIJAU DAN TEPUNG DAUN KELOR UNTUK REMAJA GIZI KURANG - Pitaloka, Ira Maya; Ma'rifah, Bahriyatul; Muhlishoh, Arwin (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground : Fulfilment of higher nutrient intake, especially protein, is needed to support the physical growth and development of undernourished adolescents. Mung bean flour and moringa leaf flour which are rich in protein, can be utilized to make dry noodles.Objectives: Knowing the effect of substituting of mung bean flour and moringa flour on the nutritional content and organoleptic properties of dry noodles.Methods : This type of research used an experimental study with a completely randomized design (RAL). Comparison of wheat flour, mung bean flour and moringa flour formulations, namely F1 (65g: 20g: 15g), F2 (60g: 25g: 15g), F3 (55g: 30g: 15g). Nutritional content data were analyzed using ANOVA test and Ducan's further test. Organoleptic test was analyzed using Kruskal Wallis test and Mann Whitney further test.Results : The results showed that the moisture content; ash content; fat; protein; carbohydrates are F1 (6.61%; 5.30%; 5.41%; 22.45%; 60.23%), F2 (5.58%; 4.25%; 4.40%; 22.90%; 62.40%), F3 (6.00%; 5.00%; 3.20%; 25.40%; 60.40%). The average results of the hedonic test are color (somewhat like), taste, aroma, texture, aftertaste, and mouthfeel (less like). The average results of hedonic quality test are color (dark green), taste (moderately bitter), aroma (moderately languorous), texture (moderately chewy), mouthfeel (not chewy), aftertaste (moderately strong). The selected formulation (F1) per serving size (70g) contained 265.58 kcal energy, 15.7g protein, 3.7g fat and 42.1g carbohydrate. F1 already fulfills % of the RDA of adolescents aged 13-15 years and can be claimed as high in protein.Conclusion : Dried noodle products can be used as an alternative high-protein food for undernourished adolescents.Keywords : Adolescents; dry noodles; moringa leaf flour; mung bean flour; underweight. ABSTRAKLatar belakang : Pemenuhan asupan zat gizi yang lebih tinggi terutama protein dibutuhkan untuk menunjang pertumbuhan fisik dan perkembangan remaja gizi kurang. Tepung kacang hijau dan tepung daun kelor yang kaya protein dapat dimanfaatkan dalam pembuatan mie kering.Tujuan : Mengetahui pengaruh substitusi tepung kacang hijau dan tepung daun kelor terhadap kandungan gizi dan organoleptik mie kering.Metode : Jenis penelitian ini menggunakan desain studi eksperimental dengan Rancangan Acak Lengkap (RAL). Perbandingan formulasi tepung terigu, tepung kacang hijau dan tepung daun kelor, yaitu F1 (65g : 20g : 15g), F2 (60g : 25g : 15g), F3 (55g : 30g : 15g). Data kandungan gizi dianalisis menggunakan uji ANOVA dan uji lanjut Duncan. Uji organoleptik dianalisis menggunakan uji Kruskal Wallis dan uji lanjut Mann Whitney. Hasil : Hasil penelitian menunjukkan bahwa kadar air; kadar abu; lemak; protein; karbohidrat yaitu F1 (6,61% ; 5,30% ; 5,41% ; 22,45% ; 60,23%), F2 (5,58% ; 4,25% ; 4,40% ; 22,90% ; 62,40%), F3 (6,00% ; 5,00% ; 3,20% ; 25,40% ; 60,40%). Hasil rata-rata uji hedonik yaitu warna (agak suka), rasa, aroma, tekstur, aftertaste, dan mouthfeel (kurang suka). Hasil rata-rata uji mutu hedonik yaitu warna (hijau tua), rasa (cukup pahit), aroma (cukup langu), tekstur (cukup kenyal), mouthfeel (tidak kenyal), aftertaste (cukup kuat). Formulasi terpilih (F1) pertakaran saji (70g) mengandung energi 265,58 kkal, protein 15,7g, lemak 3,7g dan karbohidrat 42,1g. F1 sudah memenuhi % AKG remaja usia 13-15 tahun dan dapat diklaim sebagai tinggi protein.Simpulan: Produk mie kering dapat digunakan sebagai alternatif makanan tinggi protein untuk remaja gizi kurang.Kata Kunci : Gizi kurang; mie kering; remaja; tepung daun kelor; tepung kacang hijau.